Mobility and Congestion in Urban India - Akbar, Prottoy; Couture, Victor; Duranton, Gilles; Storeygard, Adam (American Economic Review, 2023)
We develop a methodology to estimate robust city-level vehicular speed indices, exactly decomposable into uncongested speed and congestion. We apply it to 180 Indian cities using 57 million simulated trips measured by a web mapping service. We verify the reliability of our simulated trips using a number of alternative data sources, including data on actual trips. We find wide variation in speed across cities that is driven more by differences in uncongested speed than congestion. Denser and more populated cities are slower, only in part because of congestion. Urban economic development is correlated with faster speed despite worse congestion. (JEL O15, O18, R23, R41)